O fluxo operacional de prontuários e suas implicações na movimentação para consultas médicas em ambulatórios públicos - um estudo de caso múltiplo - Rocha, Paulo Augusto de Souza (2020)
Introduction: Process control in public outpatient clinics leverages contributions to management, as effective tools for organizing, evaluating and monitoring services, enabling the implementation of corrective measures aimed at the better performance of the unit; assist in defining or redefining priorities; it provides an increase in the productivity of the core activity and the rationalization of the use of resources and other managerial, administrative and legal measures that may be relevant (Ministério da Saúde, 2013). The flow of medical records within the clinic is intrinsic to the visits, in which the document is essential for the consultation to take place. Document traceability is necessary to control traffic, avoiding disruptions in information and loss of attendance to consultations, exams and procedures for patients. Therefore, the research question of the study is: What are the factors that impact the operational flows of the movement of the document from the Medical Archive Center for specialized medical care in public outpatient clinics? Objectives: The objective was to analyze the operations of handling medical records and their outcomes in specialized care in Public Outpatient Clinics, tracing the socio-cultural profile of employees; map the traceability of medical records for medical care; produce flowchart; categorize bottlenecks; consider productivity indicators and measure the average operating cost of its movement. Methodological Procedures: This is a multiple case study in the logic of investigation based on the observation of real cases with the purpose of portraying events in circumstances inherent to the process. For convenience and similarity, four public outpatient clinics were selected. In the Medical Archives, analyzes of the processes were carried out with a qualitative and quantitative approach of an exploratory nature, through bibliographic and documentary research to understand the file systems in their entirety and to support plausible hypotheses in order to contribute to the good practices of Management in Information Systems. Health. The methodology for mapping processes from the perspective of operating costs was applied based on direct observations and reports argued in the objects of study to trace the authentic flowchart of the paths taken and thus detail the processing of medical records. Results: They revealed in the socio-cultural profile that High School (68.75%), the age group of 40 to 59 years (62.50%) and activity time up to 10 years (60.42%) are the predominant indicators in all units. Operational flows are characteristic and unique. The CMRSLM handles an average of 8,000 medical records per month, devoid of a system, basically manual flow, operates 200 monthly hours, with 5 servers with a per capita income of R $ 2,280.00, performs an average of 154 consultations / office / month, takes about 05 minutes and 24s. for separation at a cost of R $ 1.43 per unit. HUSE has 9 employees and an average income of R $ 2,611.11, operates 240 hours / month, handles approximately 15,000 envelopes for consultations at the clinic per month, has a partial traceability system, simple flow, performs around 259 consultations / office / month, spends 05min for separation at a cost of R $ 1.57 per unit handled. HBDF has 19 employees who perceive an average per capita of R $ 3,568.42, works 240 hours / month, moves an average of 49,000 folders per month to the clinic, has a comprehensive traceability system, a complex flow with the participation of external medical records in its processes, performs an average of 247 consultations / consultation / month, 03min and 43s per separate unit at a cost of R $ 1.38 per unit. CHM has 14 servers with an average monthly income of R $ 2,071.43, uses 240 hours / month in its operations, handles an average of 22,000 envelopes / month for outpatient consultations, has a comprehensive traceability system, relatively simple flow, with more time for the separation of the map and well structured, it produces an average of 367 consultations / consultation / month, 05min and 34s for separation at a cost of R $ 1.32 per handled envelope. Final Considerations: The CMRSLM has inefficient traceability, favoring the duplication of document production and loss of consultations, more time for separation and intermediate cost. HUSE has structural failures, a modest and inefficient system in its control and tracking processes, which also favors the duplication of document production and failures in processing, has the highest unit operating cost. HBDF, the largest establishment among the cases, has a modular system that does not converge, complex processes that generate a delay in the constitution of the map, but efficient, which favors the quality of the dossier information, greater leaf and income per capita, consumes less time and resource in unitary movement. In CHM the flow is relatively simple, with a robust and integrated system with efficient tracking when under its tutelage, among the cases it is the one that has more time for the separation of the map, a well-structured routine linked to that of the Outpatient Clinic, with the lowest income average per server, more time for separation with lower unit cost.